Sociology Learning Design Based on Problem-Based Learning Integrated with Virtual Reality - Athiya Fara Swid; Cecep Kustandi; Uwes Anis Chaeruman (Universitas Pendidikan Ganesha, 2026)
High school students’ critical thinking skills in Indonesia remain relatively low, as evidenced by the results of the National Assessment (AKM) and various studies indicating that the majority of students are still at medium to low levels. This condition is influenced by the dominance of lecture-based teaching methods and the limited use of interactive learning media that can foster contextual analysis. This study aims to develop Sociology learning based on Problem Based Learning (PBL) integrated with Virtual Reality (VR) technology to enhance students’ critical thinking skills. The research employed the Dick and Carey instructional design model, which consists of stages such as identifying instructional goals, conducting instructional analysis, formulating objectives, developing assessment instruments, designing learning strategies, producing media, validating by experts, and conducting limited and large-scale trials. The main innovation lies in the application of branching scenarios in VR, enabling students to make decisions and directly experience the consequences within the learning process. The findings reveal that the developed media was considered highly feasible by experts, received positive responses from students, and proved more effective than conventional learning in improving critical thinking skills. These results emphasize that integrating PBL with VR has the potential to create interactive, contextual, and relevant learning experiences aligned with 21st-century education demands.